A comparative analysis of financial performance of Islamic banks vis-à-vis conventional banks: evidence from Pakistan. Issue 3 (29th July 2021) - Majeed, Muhammad Tariq; Zainab, Abida
Abstract : Purpose: In recent years, the fast growth of Islamic banks (IBs) has generated debates among policymakers and economists about the sustainability and performance of these institutions. This paper aims to undertake a comparative analysis of the financial performance of IBs and conventional banks (CBs) in Pakistan over the period 2008–2019 to evaluate how IBs are faring compared to their conventional peers. Design/methodology/approach: This paper considers Financial Ratio Analysis (FRA) to analyse and compare the performance of the top-10 IBs and CBs operating in Pakistan. The sample includes five full-fledged IBs and five CBs which offer Islamic windows in Pakistan. The top-five performing CBs offering Islamic windows have been selected in this study. Findings: The results show that IBs are better capitalized, less risky and have higher liquidity as compared to CBs. In contrast, the profits of IBs are found to be lower than those of CBs. Research limitations/implications: The study has provided an analysis of financial performance only for Pakistan. A cross-country analysis could be more representative of the performance of IBs. Practical implications: The study infers that the size of the Islamic banking industry in Pakistan should be enhanced by opening new branches and promoting Islamic financial literacy. Originality/value: The study assists investors, creditors, debtors and managers in making better decisions. It also provides the latest valuable information to regulators and policymakers that can be used to make rules and policies for the finance industry in Pakistan.